Lying, misleading, and what is said : an exploration in philosophy of language and in ethics - Saul, Jennifer Mather, 1968- (Oxford : Oxford University Press, 2013)
Jennifer Saul presents a close analysis of the distinction between lying to others and misleading them. Shedding light on key debates in philosophy of language and tackling the widespread moral preference for misleading over lying, she establishes a new view on the moral significance of the distinction.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Nov. 13, 2012).
Keywords: Truthfulness and falsehood; Language and languages -- Philosophy